THE EFFECT OF A COMBINATION OF BRISK WALKING EXERCISE AND HYDROTHERAPY ON BLOOD SUGAR LEVELS IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Priana Ziaulhaq, Dhiffa; Kartilah, Tetet; Bahtiar, Yanyan (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2025)
Diabetes mellitus is a serious, long-term, or chronic condition that cannot be cured, caused by increased blood glucose levels because the body cannot produce the hormone insulin in the right amount. This causes DM sufferers to be at risk of experiencing several complications that can be debilitating and life-threatening, resulting in an increased need for medical care. Non-pharmacological therapies that can be done as an effort to control blood sugar levels are brisk walking exercise and hydrotherapy. This study aims to determine the effect of the combination of brisk walking exercise and hydrotherapy on blood sugar levels in type 2 diabetes mellitus sufferers. The research method used was a quasi-experimental pretest-posttest design with a control group posttest. Sampling used a simple random sampling technique with a sample size of 28 people in each group. The statistical tests used were paired sample t-tests and independent sample t-tests with a significance level of 0.05. The results showed a difference in average blood sugar levels before and after exercise in the intervention group and the control group, with a p-value of 0.001. The statistical test results showed a difference in average blood sugar levels after physical exercise between the intervention and control groups, with a p-value of 0.020. This study concluded that the combination of brisk walking and hydrotherapy can reduce blood sugar levels in people with type 2 diabetes mellitus.